The Role of INPEX Masela in the Study of Children's Education in the Tanimbar Islands Regency in Higher Education - Yuliana Takdare; Lisye Salamor; Titus Gaite (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
This study aims to determine the role of INPEX Masela in the study of children's education in Tanimbar Islands Regency (KKT) in Higher Education. KKT students, what are the views of the parents of KKT students in receiving the Inpex Masela scholarship. The technique used in this research is snowball sampling. The results of the interviews showed that the INPEX Masela company, which collaborated with Pattimura University, held a scholarship program and had it handed over to students from KKT at Unpatti College. INPEX Masela is a multinational company engaged in the upstream oil and gas (oil and gas) industry. The assistance program is in two categories, namely the Tuition Fee Scholarship and Thesis Preparation Assistance Scholarship. The role and function of INPEX Masela is very important in providing educational assistance (scholarships), but seen from the operation of this program, the average KKT student did not experience the INPEX Masela scholarship assistance. Parents' point of view regarding the problem above is how INPEX is able to realize assistance by prioritizing children in KKT areas.